2020
DOI: 10.1039/d0sm01166e
|View full text |Cite
|
Sign up to set email alerts
|

Unfolding mechanism and free energy landscape of single, stable, alpha helices at low pull speeds

Abstract: Single alpha helices (SAHs) stable in isolated form are often found in motor proteins where they bridge functional domains. Understanding the mechanical response of SAHs is thus critical to understand...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 55 publications
3
5
0
Order By: Relevance
“…A filament that is stretched at a high speed shows a steeper force-extension curve and is less extensible at the same force than a filament stretched at a low speed [66,76,[85][86][87]. This loading-rate dependent force response matches, again, observations reported for the stretching of wool fibers [73] and is typical for the strain response of α helices [79]. Such a loading-rate dependent stiffening could allow cells to be protected against fast impact but to retain flexibility when slowly migrating through small spaces where they need to deform [66].…”
Section: Stretching Responsesupporting
confidence: 78%
See 1 more Smart Citation
“…A filament that is stretched at a high speed shows a steeper force-extension curve and is less extensible at the same force than a filament stretched at a low speed [66,76,[85][86][87]. This loading-rate dependent force response matches, again, observations reported for the stretching of wool fibers [73] and is typical for the strain response of α helices [79]. Such a loading-rate dependent stiffening could allow cells to be protected against fast impact but to retain flexibility when slowly migrating through small spaces where they need to deform [66].…”
Section: Stretching Responsesupporting
confidence: 78%
“…At high extensions, the slope is increased with respect to the plateau regime (III). This three-regime stretching is reminiscent of the response of α helices and coiled-coils to stretching [76][77][78][79], which indicates that the shape of the force-strain curve originates from structural changes in the filament. Early studies of the extension behavior of wool and hair with wide-angle X-ray scattering (WAXS) already revealed that the coiled-coil and α-helical contributions reduce upon stretching, and a new feature appears in the diffraction pattern that is characteristic of β sheets [74,[80][81][82].…”
Section: Stretching Responsementioning
confidence: 93%
“…It is critical to note that not all types of charge patterning previously examined in the context of IDP conformation give rise to a disordered polymer-like protein conformation. , Recently, one such type of charge pattern has been demonstrated to exist in the highly helical protein domains [termed single-stable α helix (SAH) or polyampholyte helix]. Remarkably, natural polyampholyte helices, unusually rich in charged amino acids, are found to closely follow a charge pattern represented by alternating blocks of four positively charged monomers [consisting of lysine (Lys or K) and arginine (Arg or R)], followed by four negatively charged monomers [glutamic acid (Glu or E)], ((K/R) 4 E 4 ) n . Here, the favorable interactions between the oppositely charged side chains enabled by this precise charge patterning help to stabilize the helical structures …”
Section: Introductionmentioning
confidence: 99%
“…A filament that is stretched at a high speed shows a steeper force-extension curve and is less extensible at the same force than a filament stretched at a low speed [65,76,[85][86][87]. This loading-rate dependent force response matches, again, observations reported for the stretching of wool fibers [73] and is typical for the strain response of α helices [79]. Such a loading-rate dependent stiffening could allow cells to be protected against fast impact but to retain flexibility when slowly migrating through small spaces where they need to deform [65].…”
Section: Stretching Responsesupporting
confidence: 78%